2013
DOI: 10.1111/aji.12184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxychloroquine on Antiphospholipid Antibody‐Induced Changes in First Trimester Trophoblast Function

Abstract: ProblemWomen with antiphospholipid syndrome (APS) are at risk for pregnancy complications. Antiphospholipid antibodies (aPL) alter trophoblast function by triggering an inflammatory cytokine response; modulating angiogenic factor secretion; and inhibiting migration. While patients with APS are often treated with hydroxychloroquine (HCQ), its effect on trophoblast function is poorly understood.Method of study A human first trimester trophoblast cell line was treated with or without antihuman b 2 GPI mAbs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 57 publications
4
60
0
Order By: Relevance
“…Trophoblast migration and invasion are regulated by the balance between the production of the matrix metalloproteinases and their tissue inhibitors, TIMP1 and TIMP2. aPL induced the secretion of TIMP2 diminishing the ability of trophoblast to migrate [29]. Consistent with this, we have previously showed that purified polyclonal IgG from pregnancy morbidity but not vascular thrombosis was able to inhibit the migration of human trophoblast cells [30].…”
Section: Discussionsupporting
confidence: 58%
“…Trophoblast migration and invasion are regulated by the balance between the production of the matrix metalloproteinases and their tissue inhibitors, TIMP1 and TIMP2. aPL induced the secretion of TIMP2 diminishing the ability of trophoblast to migrate [29]. Consistent with this, we have previously showed that purified polyclonal IgG from pregnancy morbidity but not vascular thrombosis was able to inhibit the migration of human trophoblast cells [30].…”
Section: Discussionsupporting
confidence: 58%
“…Hydroxychloroquine (HCQ) provides another option in refractory obstetric APS: its addition to standard treatment allowed a decrease in the rate of pregnancy wastage from 81 to 19% [33 & ]. Such clinical efficacy is consistent with its well known in-vitro properties: HCQ not only reduces aPL binding to syncytiotrophoblasts and restores the placental expression of AnnexinA5 [25 && ], but also downregulates TLR4 expression, thus preventing the antib2GPI antibody-induced impairment of trophoblast differentiation [34] and reverses aPL-induced inhibition of pro-migratory IL-6, thus enhancing trophoblast migration [35].…”
Section: Obstetric Antiphospholipid Syndromesupporting
confidence: 66%
“…Recent studies have reported that HCQ reduces the binding of aPL-b2GPI complexes in trophoblast surface [128,129]. The use of HCQ was recently associated with a higher rate of live births and a lower frequency of overall aPL-related pregnancy complication [130].…”
Section: Lupus and Apl Positivity/antiphospholipid Syndromementioning
confidence: 99%